2010
DOI: 10.1002/yea.1783
|View full text |Cite
|
Sign up to set email alerts
|

A systematic CEN library of the Saccharomyces cerevisiae genome

Abstract: Progress in modern genetics is greatly facilitated by systematic resources that enable rapid and comprehensive analysis. Here we report the creation of a nearly complete systematic low-copy (CEN URA3) library of the Saccharomyces cerevisiae genome that complements existing systematic high-copy libraries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…To test whether this phenotypic toggle is in fact modulated by the copy number variation of specific genes, we transformed the original F45 (fluffy) strain with a set of low copy plasmids containing portions of chromosome XVI (34). This screen identified a plasmid containing seven full-length genes that was able to confer the smooth state (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether this phenotypic toggle is in fact modulated by the copy number variation of specific genes, we transformed the original F45 (fluffy) strain with a set of low copy plasmids containing portions of chromosome XVI (34). This screen identified a plasmid containing seven full-length genes that was able to confer the smooth state (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the gene responsible for the phenotypic switch was easily identified (Tan et al ., ). This exemplifies the benefit of well‐annotated functional genomics data and a plasmid library of the yeast genome (Hvorecny & Prelich, ) in unraveling the molecular mechanism by which an aneuploid karyotype confers a particular phenotype.…”
Section: Future Perspectivementioning
confidence: 86%
“…(2) We tested all strains for synthetic lethality with the prp5-SAT-to-GAR allele, which has severely reduced ATPase activity (Xu and Query 2007), identifying seven such strains. We then used a genomic library (Hvorecny and Prelich 2010) to rescue the synthetic lethality. All genomic plasmids that rescued viability carried PRP9 (a U2 snRNP SF3a component), and subsequent sequencing of the PRP9 locus in these strains revealed that all carried an R341K mutation.…”
Section: Mds and Cll Mutations In Sf3b1 Alter Splicing Of Suboptimal mentioning
confidence: 99%